Photo-induced semimetallic states realised in electron–hole coupled insulators - Kozo Okazaki (Nature Portfolio, 2018)
Ultrafast light pulses can manipulate and probe materials faster than relaxation timescales, leading to new electronic states and insights into equilibrium properties. Okazaki et al. use the properties of photo-induced metallic states to investigate unconventional correlated behaviour in Ta2NiSe5 and Ta2NiS5.